Micropropagation and in vitro short-term storage of Globba sherwoodiana W.J. Kress & V. Gowda - Muktawapai, Kittikun; Wongchaochant, Shermarl (Agriculture and Natural Resources, 2020)
Globba sherwoodiana is an important cut-flower plant in Thailand which is still cultivated using conventional vegetative propagation. In vitro culture is a useful technique for increasing the efficiency of plant production and breeding programs. This research studied suitable culture media for G. sherwoodiana micropropagation and in vitro storage with genetic fidelity analysis. The sterile shoots were cultured on semi-solid Murashige and Skoog (MS) medium supplemented with 30 different treatments of 6-benzylaminopurine (BA) or 1-naphthaleneacetic acid (NAA). The results showed that explants cultured on MS medium supplemented with a concentration of BA higher than 2 mg/L could induce significantly higher numbers of new shoots, but they were hyperhydric. The explants cultured on MS medium supplemented with a concentration of NAA lower than 1.5 mg/L could induce significantly higher numbers of normal roots. The most suitable medium for shoot proliferation was MS medium supplemented with 1 mg/L BA, while MS medium supplemented with a concentration of NAA lower than 1 mg/L was suitable for root induction. For short-term storage culture, the single shoot explants were cultured on medium of semi-solid MS, ½ MS or ¼ MS supplemented with 10 g/L, 20 g/L, 30 g/L, 40 g/L or 50 g/L sucrose for 60 d, 120 d and 180 d. After storage, the stored explants were recovered by transferring to MS medium and suitable slow growth media were evaluated based on the growth rate, percentage of plantlet survival and new shoot proliferation after recovery. No polymorphic band profiles were found in the clones analyzed using inter simple sequence repeats at the end of each storage period.